Territórios de identidade e políticas públicas na Bahia: gênese, resultados, reflexões e desafios - Dias, Wilson José Vasconcelos (2017)
This paper aims to record the constitution and consolidation process of the 27 Identity Territories in the state of Bahia, with its 417 municipalities in the period from 2003 to 2016, as well as listing and analyzing the main results in the implementation of sectoral public policies that consider these territories as units of planning and implementation of government actions. It also aims to confront what happened in Bahia in this period with the literature that covers the subject of territories, territorialities and related subjects, such as social management of development and rurality. At the end, points challenges through propositions to keep using methodological tools that consolidate the territorial approach as the most adequate to promote changes and social transformation, from the local, with effective participation of the population in the elaboration and operationalization of inclusive public policies that favor the creation and / or increment of income and improvement of people's quality of life.